2013
DOI: 10.1007/s10461-013-0660-4
|View full text |Cite
|
Sign up to set email alerts
|

Prevalence of HIV Infection and Risk Behaviors Among Younger and Older Injecting Drug Users in the United States, 2009

Abstract: This study compared HIV sero-prevalence and risk behaviors between younger and older injecting drug users (IDUs). IDUs aged ≥18 years were interviewed for the 2009 National HIV Behavioral Surveillance System. Using GEE regression, we assessed characteristics of younger (18–29 years) and older (≥30 years) IDUs, and factors associated with past 12-month receptive syringe sharing and unprotected sex (vaginal/anal). Of 10,090 participants, 10 % were younger. HIV sero-prevalence was lower among younger than older I… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

3
23
0
2

Year Published

2014
2014
2019
2019

Publication Types

Select...
7

Relationship

1
6

Authors

Journals

citations
Cited by 45 publications
(28 citation statements)
references
References 82 publications
3
23
0
2
Order By: Relevance
“…As in prior studies (Armstrong, 2007; Broz and Ouellet, 2008; Broz et al, 2014; Garfein et al, 1998; Hahn et al, 2010; Neaigus et al, 2006; Ochoa et al, 2001; Prussing et al, 2014; Pugatch, 2006), our study showed that young PWID are likely to be non-Hispanic white (71%), even though our recruitment sites were located in urban, predominantly African American and Hispanic neighborhoods. A main finding of our study is that homelessness and residential transience are integral components of HCV and HIV risk, mediated through network size and syringe sharing.…”
Section: Discussionsupporting
confidence: 71%
See 3 more Smart Citations
“…As in prior studies (Armstrong, 2007; Broz and Ouellet, 2008; Broz et al, 2014; Garfein et al, 1998; Hahn et al, 2010; Neaigus et al, 2006; Ochoa et al, 2001; Prussing et al, 2014; Pugatch, 2006), our study showed that young PWID are likely to be non-Hispanic white (71%), even though our recruitment sites were located in urban, predominantly African American and Hispanic neighborhoods. A main finding of our study is that homelessness and residential transience are integral components of HCV and HIV risk, mediated through network size and syringe sharing.…”
Section: Discussionsupporting
confidence: 71%
“…Studies frequently report associations between HCV infection and injection duration, injection frequency, cocaine injection, and sharing of syringes and other injection paraphernalia among persons who inject drugs (PWID; Boodram et al, 2010; Falster et al, 2009; Garfein et al, 1996; Hagan et al, 2001; Pouget et al, 2012; Thorpe et al, 2000). Recent trends show that although both HIV (Broz et al, 2014; Centers for Disease Control and Prevention, 2009) and HCV (Amon et al, 2008) prevalence have steadily declined among older PWID, high-incidence of HCV infection (Page et al, 2009; Zibbell et al, 2015) and HCV outbreaks among younger PWID (Centers for Disease Control and Prevention, 2011; Leuchner et al, 2008) are occurring. In addition, IDU has been steadily increasing among youths (Chatterjee et al, 2011; Tempalski et al, 2013), and high levels of risky injection and sex behaviors continue to be reported in this group (Broz et al, 2014; Hahn et al, 2010; Rondinelli et al, 2009).…”
Section: Introductionmentioning
confidence: 99%
See 2 more Smart Citations
“…Black PWID tend to be older, and fewer report sharing syringes than do Hispanics or whites (12). Encouraging trends in use of SSPs and receipt of all syringes from sterile sources contribute to reducing the risk for HIV among black PWID.…”
Section: Conclusion and Commentsmentioning
confidence: 99%